Phytochemical Screening and Antimicrobial Properties of a Common Brand of Black Tea (Camellia sinensis) Marketed in Nigerian Environment - Olosunde O. Funmilayo; Abu-Saeed Kamaldeen; Abu-Saeed Muhammad Buhari (Tabriz University of Medical Sciences, 2012)
Purpose: This study is aimed at determining chemical constituents and antimicrobial activities of a common brand of black tea (Lipton®) in Nigeria. Methods: Standard methods were employed for testing carbohydrates, tannins, saponins, flavonoids, alkaloids, steroids and terpenes in the tea. Antimicrobial activities of methanolic and aqueous extracts of the tea on four standard strains of organisms: Escherichia coli, Pseudomonas aeruginosa, Staphylococcus aureus and Bacillus subtilis were also determined by standard methods. Results: Results showed that the tea contains tannin and reducing sugar. Concentrations of 1%, 2%, 4%, 6%, 8% and 10% aqueous and methanolic extract of black tea were prepared and their zones of inhibition determined against the four test organisms using the cup plate method. This was compared with zones for standard disc Gentamicin (10 μg) and Erythromycin (15 μg). Pseudomonas aeruginosa was sensitive to 2% to 10% aqueous extracts and intermediate to 6%, 8% and 10% methanolic extracts. E. coli was intermediately sensitive to 6%, 8% and 10% aqueous extract and 2% to 10% methanolic extracts. B. subtilis was intermediately sensitive to 4%, 6% and 8% aqueous extract and 4% to 10% methanolic extract but sensitive to 10% aqueous extract. Staph.aureus was intermediately sensitive to 4% to 10% aqueous extracts and 2% to 10% methanolic extracts. B. subtilis had the lowest MIC values of both aqueous and methanolic extracts. Conclusion: In conclusion, this study has shown that Lipton® has antimicrobial properties on E.coli, Staph.aureus, B.subtilis and Ps.aeruginosa and contains tannin and reducing sugar.